Rural Area Planning and Development Mechanisms - Yusri, Mohammad (Lembaga Riset Mutiara Akbar, 2024)
Community participation in governance is often emphasized but difficult to implement effectively. In rural development, meaningful participation is essential for sustainable outcomes. However, in practice, many development policies are still formulated in a top-down manner without adequate community involvement, making them less effective and mismatched with local needs. This study aims to analyze the mechanism of village development planning in Abuki District and evaluate the extent of community involvement in the process. Using a qualitative descriptive approach, data were collected through observation, document analysis, and in-depth interviews with village officials and community representatives. The findings indicate that the village development planning team, formed based on Minister of Home Affairs Regulation No. 114 of 2015, has not fulfilled its role optimally. Planning procedures are often simplified, and community participation remains minimal. In addition, coordination among village institutions is weak, leading to ineffective planning and implementation. This research highlights the need for more participatory and well-coordinated planning mechanisms to ensure that development programs align with the actual needs and aspirations of the rural population.